Design of gem‐Difluoro‐bis‐Tetrahydrofuran as P2 Ligand for HIV‐1 Protease Inhibitors to Improve Brain Penetration: Synthesis, X‐ray Studies, and Biological Evaluation. Issue 1 (21st October 2014) - Ghosh, Arun K.; Yashchuk, Sofiya; Mizuno, Akira; Chakraborty, Nilanjana; Agniswamy, Johnson; Wang, Yuan‐Fang; Aoki, Manabu; Gomez, Pedro Miguel Salcedo; Amano, Masayuki; Weber, Irene T.; Mitsuya, Hiroaki
Abstract The structure‐based design, synthesis, biological evaluation, and X‐ray structural studies of fluorine‐containing HIV‐1 protease inhibitors are described. The synthesis of both enantiomers of the gem‐difluoro‐bis‐THF ligands was carried out in a stereoselective manner using a Reformatskii–Claisen reaction as the key step. Optically active ligands were converted into protease inhibitors. Two of these inhibitors, (3R, 3aS, 6aS)‐4, 4‐difluorohexahydrofuro[2, 3‐b]furan‐3‐yl(2S, 3R)‐3‐hydroxy‐4‐((N‐isobutyl‐4‐methoxyphenyl)sulfonamido)‐1‐phenylbutan‐2‐yl) carbamate (3) and (3R, 3aS, 6aS)‐4, 4‐difluorohexahydrofuro[2, 3‐b]furan‐3‐yl(2S, 3R)‐3‐hydroxy‐4‐((N‐isobutyl‐4‐aminophenyl)sulfonamido)phenylbutan‐2‐yl) carbamate (4), exhibited HIV‐1 protease inhibitory Ki values in the picomolar range. Both 3 and 4 showed very potent antiviral activity, with respective EC50 values of 0.8 and 3.1 nM against the laboratory strain HIV‐1LAI. The two inhibitors exhibited better lipophilicity profiles than darunavir, and also showed much improved blood–brain barrier permeability in an in vitro model. A high‐resolution X‐ray structure of inhibitor 4 in complex with HIV‐1 protease was determined, revealing that the fluorinated ligand makes extensive interactions with the S2 subsite of HIV‐1 protease, including hydrogen bonding interactions with the protease backbone atoms. Moreover, both fluorine atoms on the bis‐THF ligand formed strong interactions with the flap Gly 48 carbonyl oxygen atom.